Neumonía intersticial por pneumocystis carinii - Rodríguez-Vigil, Emilio; Zomeño, Mariano; Soler Regal, María C.; Martín Aguado, María J.; López Sastre, José; Cotero Lavín, Ángel (Revista Cubana de Pediatría, 2023)
Sobre la existencia de este parásito en la península ibérica.